Formulation and Investigation of Lacidipine as a Nanoemulsions - Rajaa A. Dahash; Nawal A. Rajab (College of Pharmacy University of Baghdad, 2020)
Many pharmaceutical molecules have solubility problems that until yet consist a hurdle that restricts their use in the pharmaceutical preparations. Lacidipine (LCDP) is a calcium-channel blocker with low aqueous solubility and bioavailability.         Lipid dosage forms are attractive delivery systems for such hydrophobic drug molecules. Nanoemulsion (NE)  is one of the popular methods that has been used to solve the solubility problems of many drugs. LCDP was formulated as a NE utilizing triacetin as an oil phase, tween 80 and tween 60 as a surfactant and ethanol as a co-surfactant. Nine formulas were prepared, and different tests performed to ensure the stability of the NEs, such as thermodynamic stability, particle size, Polydispersity index, zeta potential, dye solubility test, dilution test, drug content test and in-vitro drug release. Results of characterization showed that LCDP NE (F-5) with (oil: Smix (3:1):DDW (10:60:30)) ratio was selected as a best formula, since it have excellent thermodynamic stability with a particle size of 13.42, low PDI 0.234 , zeta potential (-14.5mV), efficient electrical    conductivity  0.241ms/cm , good pH value (5.9), good percent of light transmittance (99.10%) , with  acceptable viscosity , higher percent of drug content (99.14%) and complete release of the drug after (30 min.) with significantly higher (P<0.05)   dissolution rate in comparison with pure drug powder.      From the results obtained NE was found to be an efficient method to enhance the solubility and dissolution rate of drugs that have poor water solubility (lipophilic drugs).